Mathematics Student Teachers’ Reflections on Their Preparation Of Ethnomathematics Approach: A Community Cultural Wealth Perspective - Mabotja, Koena Samuel (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
The purpose of this article was to explore student teachers’ reflections on their preparation on ethnomathematics approaches based on their participation in one-day ethnomathematics workshop. This article emanate from the literature concern that pre-service mathematics teacher education is lamented for not equipping teachers with pedagogical knowledge and skills to contextualise mathematics topics through ethnomathematics approach. Mathematics student teachers complete their initial teacher education with underdeveloped knowledge of ethnomathematics and its implications in mathematics classrooms. In this article, which uses parts of the author’s doctoral study qualititaive research approach is adopted. A case study design was adopted to gain indepth student teachers’ reflections on the phenomenon under investigation. Purposive sampling was used to select 10 mathematics education student teachers enrolled in a 4-year Bachelor of Education in foundation phase, senior phase, and FET phase programmes. Focus group interviews was used as a data collection technique. The results of student teachers’ reflections are presented in three themes which emerged from this research: (1) ethnomathematics ushers pedagogical shift from traditional to innovative teaching approaches; (2) ethnomathematics approaches develop student teachers’ awareness of mathematics embedded in Morabaraba game; and (3) Integration of cultural techniques provide multiple strategies for teaching and learning multiplication concept. This article concludes that the ethnomathematics workshop successfully enhanced the understanding of mathematics student teachers regarding the use of cultural resources in mathematics learning. Keywords: ethnomathematics, contextualisation, student teachers, cultural resources, pre-service mathematics teacher education.